Analisis Faktor Yang Mempengaruhi Return Saham Perusahaan Sektor Perbankan Pada Saat Pandemi Covid 19: (Studi Khasus Di Bei Periode 2020-2021) - Rizki Novianto Kasim; Asrudin Hormati; Gregorius Jeandry (AKUNTANSI 45, 2023)
This study aims to determine the factors that influence stock returns, especially in Peranakan sector companies listed on the Indonesian Stock Exchange. The factors are Non Performing Laon, Loan to deposit ratio, and Capital Adequacy Ratio. The population in this study is the role-playing sector companies listed on the Indonesian stock exchange during the study period. The sampling method used in this study is all quarterly financial reports of banking sector companies listed on the Indonesian stock exchange without using certain sample criteria. This test uses panel data analysis (panel pooled data) to examine the effect of two or more independent (explanatory) variables on a dependent variable. The results of this study indicate that the Non-Performing Laon variable has no effect on stock returns, while the Loan to deposit ratio variable has no effect on stock returns, and also the Capital Adequacy Ratio variable has no effect on stock returns.